Human Sexuality - Sultan Sheriff, Dhastagir (IntechOpen, 2022)
Sexuality involves anatomical, physiological, psychological, developmental, cultural, and relational factors. These may vary from individual to individual depending upon gender identity, orientation, intention, desire, arousal, orgasm, and emotional satisfaction.The sexual response cycle involves different phases, including excitement, plateau, orgasm, and resolution. These phases may not be the same or follow the same order in different people. This book deals with the origins of human sexuality, sex development, gender, sexual health, sexuality, and disability. The book also gives a bird's eye view of how the COVID-19 pandemic affected human sexuality.